Crisis of core values in modern Olympic sports - Sobyanin, F. I.; Irkhin, V. N.; Nikulina, T. B.; Peresypkin, A. P. (Theory and Practice of Physical Culture, 2018)
The article analyzes the ongoing crisis and negative trends in the modern Olympic sports. Objective of the study was to give an account of the values degrading process in the modern Olympic sports and attitudes to them - to overview the fundamental reasons for the crisis of the modern Olympic sports. The study classifies the Olympic sport values into common human values, international and national Olympic sport values; analyzes the values degrading process in the modern societies; and lists the key negative trends in the Olympic sports including: biased refereeing service; discriminatory attitudes to individual athletes and national teams; doping related problems; financial abuse related scandals; dirty politicking in sports; violations of the relevant international laws; violations of the core principles set forth by Pierre de Coubertin and the valid Olympic Charter. Based on the study data, the core reasons for the values system crisis in the modern Olympic sports are outlined including the global humanitarian crisis; sport politicization and commercialization processes; and the global sport system mismanagement.